Konsep Zuhud dalam Pemikiran Hamka dan al-Qushayri: Studi Komparatif Perspektif Modern dan Klasik - Lita Siti Latifah; Yumna Yumna; Naan Naan (Gunung Djati Conference Series, 2023)
In historical records, the concept of zuhud has developed meaning from various paradigms which say that the concept of zuhud which avoids worldly life is zuhud which does not avoid worldly life. The existence of this development of meaning is an interesting thing to examine further. This paper aims to analyze the comparison of the concept of zuhud according to Hamka and Al-Qushayri. The research method used is library research. Thus, the basic analysis used by the author is the method of content analysis (content analysis). The conclusion from this study states that the concept of zuhud according to al-Qusyairi's view is the concept of zuhud, avoids fame and crowds. While the concept of zuhud Hamka is a concept that reflects the attitude of not avoiding the world with the meaning of life in socializing in society. The similarities between the two thoughts of al-Qusyairi and Hamka lie in their thoughts on the love of the world, wealth and throne which is the cause of human negligence from Allah SWT. While the point of difference between the two thoughts of these figures, namely, namely the attitude of not being proud nor avoiding the world and not grieving for what escapes the worldly. Zuhud attitude also encourages someone to always be wise in dealing with every problem. Meanwhile, Hamka's zuhud formula has a free meaning, meaning that if you are rich or poor, something material will not hinder someone from having a relationship with God.